Hazardous waste engineering and management : (Chongrak Polprasert Environmental Engineering Program Asian Institute of Technology Bangkok, 1989)
According to RCRA ,a hazardous waste is a solid waste which can be in the forms of solid, semi-solid liquid or gas. In general, hazardous waste are those that pose a substantial danger immediately or over a period of time to human, animal or plant lives; Problems caused by hazardous wastes,...